The Impact of Human Resources Strategies in the Administrative Empowerment: A Case Study in Arabian Qatrana Cement - Al-Qatawneh, Aymn Sulieman Zamel; Mobaideen, Walaa (International Review of Management and Marketing, 2017)
This study aims to identify the impact of human resources strategies in administrative empowerment in the Arabian Qatrana Cement Company, and to achieve the goal of the study by using a questionnaire instrument, which is consisted of (29) items. The research instrument was carefully developed and its validity and reliability were verified, the study was applied to a sample of the company’s employees who totaled (95) employees. After the analysis, the results revealed that the implementation level of human resources strategies was high, as the arithmetic mean was (4.57) and standard deviation equaled (0.53), which may attributed to the company’s interest in the application of human resources strategies. The results has shown that the application level of administrative empowerment at the company was also high, as the arithmetic mean was (4.53) and the standard deviation equaled (0.54) since the company is working in order to enable the employees to find a work environment characterized by freedom and independency. The study concluded that there is a statistically significant impact at of human resources strategies by its dimensions (selection and placement strategy, compensation strategy, training and development strategy and performance evaluation strategy) in administrative empowerment in Arabian Qatrana Cement Company. In light of the results of this study, the researcher recommended to develop a comprehensive strategy for human resources in Arabian Qatrana Cement Company in line with the improvement of policies and procedures relating to the selection and placement of employees, and to develop their abilities, preparing the right climate that contributes to raising their morale and creating trust between managers and employees so as to carry out their work within the standards and their participation in decision-making process. Keywords: Human Resources Strategies, Administrative Empowerment, Arabian Qatrana Cement JEL Classifications: D73, O15